Dampak Stabilitas Ekonomi terhadap Pertumbuhan Ekonomi Jangka Panjang - Dede Yurahman; Doni Satria (Universitas Negeri Padang, 2025)
Economic stability plays a crucial role in ensuring long-term economic growth and the well-being of a country. This study examines the impact of economic stability on long-term economic growth by analyzing key variables such as interest rates, population growth, capital accumulation, and technological advancements. Utilizing panel data regression analysis, this research finds that economic stability significantly contributes to long-term economic growth by reducing population growth volatility and providing a conducive investment environment. Additionally, technological advancements and capital accumulation play vital roles in enhancing economic productivity. The findings suggest that policymakers should prioritize economic stability to ensure sustainable economic growth in the future